The Book of Pontiffs : (Liber Pontificalis) : the ancient biographies of the first ninety Roman bishops to AD 715 - Davis, Raymond; Davis, Raymond; Davis, Raymond (Translated texts for historians ;, 2010)
No complete translation of the Latin text of the Book of Pontiffs - the Liber Pontificalis of the Roman Church - exists in any language, though the work is indispensable to students of late antiquity and the early middle ages; this book provides an english version of the first ninety papal biographies, from St Peter down to AD 715. These lives were first compiled in the sixth century and then regularly brought up to date. In them the reader will find the curious mixture of fact and legend which had come by the Ostrogothic period to be accepted as history by the Church in Rome, and also the subsequent records maintained through to the early eighth century while Rome was under Byzantine sovereignty. In no sense was the Liber Pontificalis an ‘official’ chronicle of these centuries, and there emerge throughout the interests and prejudices of compilers who belonged, it seems, to the lower levels of the papal administration.